Exploring Talent Retention Strategies in Local Government Institutions of Makassar: A Phenomenological Study - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This phenomenological study examines the lived experiences of talent retention strategies within Makassar's local government institutions, exploring how cultural values, organizational climate, and leadership styles influence employee commitment in the Indonesian public sector context. Through in-depth interviews with 15 participants comprising HR managers and employees across various government departments, the research investigates the subjective meanings and experiences that shape talent retention decisions. Using Colaizzi's seven-step phenomenological analysis framework, the study identified five essential themes: Cultural Harmony and Collective Belonging, Leadership Authenticity and Emotional Connection, Professional Growth Within Bureaucratic Constraints, Work-Life Integration and Family Values, and Service Purpose and Community Impact. The findings reveal that talent retention in Makassar's local government is fundamentally shaped by the integration of traditional Bugis-Makassar cultural principles—sipakatau (mutual respect), sipakalebbi (mutual honoring), and sipakainge (mutual remembrance)—with contemporary organizational practices. Participants emphasized the significance of authentic leadership characterized by "kepedulian yang tulus" (genuine care) and meaningful work that contributes directly to community development. The study demonstrates that effective retention strategies must acknowledge employees as whole persons whose professional commitments are inseparable from their cultural identity, family relationships, and community connections. These findings challenge Western-centric talent management models by revealing how culturally-embedded values serve as more powerful retention mechanisms than purely economic incentives. The research contributes to developing culturally-responsive talent management frameworks for Indonesian local governments, emphasizing the need for relationship-centered, purpose-driven approaches that honor local wisdom while addressing contemporary human resource challenges in public sector organizations.